There are two ways to work this out: normal variables or using "imaginary" numbers.
Normal variables:
![(7+2i)(3-i)\\(7*3)+[7*(-i)]+(3*2i)+[2i*(-i)]\\21-7i+6i-2i^{2}\\\\21-i-2i^{2}](https://tex.z-dn.net/?f=%20%287%2B2i%29%283-i%29%5C%5C%287%2A3%29%2B%5B7%2A%28-i%29%5D%2B%283%2A2i%29%2B%5B2i%2A%28-i%29%5D%5C%5C21-7i%2B6i-2i%5E%7B2%7D%5C%5C%5C%5C21-i-2i%5E%7B2%7D)
Imaginary numbers:
Using the result from earlier:
![21-i-2i^{2}](https://tex.z-dn.net/?f=21-i-2i%5E%7B2%7D)
Now since
![i = \sqrt{-1}](https://tex.z-dn.net/?f=%20i%20%3D%20%5Csqrt%7B-1%7D)
, then the expression becomes:
the solution is here,
the coordinate of centre of circle A is (3,2)
and the coordinate of centre of circle B is (3,0).
so the translation point from A to B is (3-0,0-2)=(3,-2).
Now the translation rule is given by (x+h,y+k)
where h is the tranalation anlong the x-axis and k is the translation along the y-axis.
For this problem, translation ruleis (x+3,y-2).
Then, radius of circle A(r1)=2 units
radius of circle B (r2)= 3 units
as the circle A is translated to B, the scale factor is
r2/r1=3/2=1.5
In conclusion, the translation rule for given circles is (x+3,y-2) and its scale factor is 1.5
We subsituete
9:6=6:4
treat as fraction
9/6=6/4
9/6=3/3 times 3/2
6/4=2/2 times 3/2
3/2=3/2
this is TRUE
Answer:
C. I & III
Step-by-step explanation:
I simplifies to ...
2(6x +15 -5x) +4 = 40
12x +30 -10x +4 = 40
2x +34 = 40
__
II simplifies to ...
40 = 2(15 -x) +4
40 = 30 -2x +4
40 = -2x +34 . . . . . . not equivalent to I (sign of x-term is different)
__
III simplifies to ...
12x +30 -10x +4 = 40
2x +34 = 40 . . . . . . equivalent to I
___
I & III are equivalent